2017
DOI: 10.1155/2017/1428943
|View full text |Cite
|
Sign up to set email alerts
|

Electroacupuncture for Functional Constipation: A Multicenter, Randomized, Control Trial

Abstract: Background and Aim. To investigate the efficacy and safety of electroacupuncture (EA) with different current intensities for functional constipation (FC) and to assess whether the effects of EA with different current intensities are superior to the mosapride. Methods. Patients with FC were randomly divided into low current intensity group (LCI), high current intensity group (HCI), and mosapride group (MC). The primary outcome was three or more spontaneous bowel movements (SBMs) per week and an increase of one … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 45 publications
1
17
0
2
Order By: Relevance
“…A recent report compared 16 sessions of EA over 4 weeks with mosapride, 5 mg three times a day, and demonstrated ≥3 SBM in 66% and 52% of participants, respectively 5. In this study, EA resulted in ≥3 CSBM at similar rates as prucalopride 6.…”
Section: Implications For Practicesupporting
confidence: 57%
“…A recent report compared 16 sessions of EA over 4 weeks with mosapride, 5 mg three times a day, and demonstrated ≥3 SBM in 66% and 52% of participants, respectively 5. In this study, EA resulted in ≥3 CSBM at similar rates as prucalopride 6.…”
Section: Implications For Practicesupporting
confidence: 57%
“…e included studies came from Korea and China and were published between 2010 and 2019. e diagnostic criteria of one RCT were the guidelines for clinical research [44], and the other RCTs were Rome III. ere was 1 four-arm RCT [55], 5 three-arm RCTs [49][50][51][52][53][54], and 23 two-arm RCTs . e treatment duration was set for 2 weeks in 2 studies [32,46], 3 weeks in 1 study [47], 4 weeks in 18 studies [27, 30, 31, 33-37, 42, 44, 45, 48-55], and 8 weeks in 7 studies [26,28,29,[38][39][40][41]43].…”
Section: Characteristics Of the Studiesmentioning
confidence: 99%
“…e treatment duration was set for 2 weeks in 2 studies [32,46], 3 weeks in 1 study [47], 4 weeks in 18 studies [27, 30, 31, 33-37, 42, 44, 45, 48-55], and 8 weeks in 7 studies [26,28,29,[38][39][40][41]43]. For these 28 trials, 10 trials reported CSBM [26-28, 36, 38-43, 46], 13 trials reported BSFS [27-29, 34, 35, 38-43, 47, 48, 53], 9 trials presented responder rate [26, 28, 29, 38-41, 43, 47, 53], 6 trials presented CSS [30,45,[48][49][50][51][52], 10 trials mentioned PAC-QOL [28,32,33,37,38,41,43,44,46,53], and 15 trials mentioned safety evaluation [26][27][28][29][30][31][32][33][49][50][51][52][53][54][55]. Table 2 summarizes the other parameters of the i...…”
Section: Characteristics Of the Studiesmentioning
confidence: 99%
“…Studies indicated that EA could promote the colonic motility, 4,5 thus effectively alleviating symptoms in functional constipation patients. 6 Previous work using diabetic animal models has demonstrated that EA at ST36 was able to multiply the ICC of intestine. 7,8 However, the source of increased ICC has not been clearly illustrated.…”
Section: Introductionmentioning
confidence: 98%
“…Relatively, electroacupuncture (EA) may be a potentially effective therapeutic method to clinically treat intestinal functional diseases. Studies indicated that EA could promote the colonic motility, thus effectively alleviating symptoms in functional constipation patients . Previous work using diabetic animal models has demonstrated that EA at ST36 was able to multiply the ICC of intestine .…”
Section: Introductionmentioning
confidence: 99%